jonnburton
Junior Member
- Joined
- Dec 16, 2012
- Messages
- 155
Hi,
I was wondering if anyone could tell me where I went wrong with trying to find the following inverse function:
\(\displaystyle h(x) = x^2 -3\)
so
\(\displaystyle y = x^2 - 3\)
adding 3 to both sides:
\(\displaystyle y +3 = x^2\)
\(\displaystyle x = \sqrt{y+3}\)
\(\displaystyle h^{-1}(x) = \sqrt{x+3}\)
However, the books answer says that \(\displaystyle h^{-1}(x) =- \sqrt{x+3}\)
I was wondering if anyone could tell me where I went wrong with trying to find the following inverse function:
\(\displaystyle h(x) = x^2 -3\)
so
\(\displaystyle y = x^2 - 3\)
adding 3 to both sides:
\(\displaystyle y +3 = x^2\)
\(\displaystyle x = \sqrt{y+3}\)
\(\displaystyle h^{-1}(x) = \sqrt{x+3}\)
However, the books answer says that \(\displaystyle h^{-1}(x) =- \sqrt{x+3}\)